Market share analysis of Berger Paints BD Ltd. (BPBL) at Mirpur DOHS - Shakeer, Imam (BRAC University, 2012)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2011.